Qual o valor dos serviços ecossistêmicos culturais de sítios arqueológicos rupestres? - Albuquerque, Cleberson Carlos Xavier de (2021)
The valuation of ecosystem cultural services has been debated more intensively in the academic community, especially after the major environmental impacts that have occurred recently in our country,such as: Brumadinho and the Samarco dam, where ore tailings dams are broken and invaded water courses, with the worsening of the Samarco dam, invaded the Doce river, destroying natural and cultural heritage in its course.. But what would this economic valuation? This sentence raises questions about which spheres of the environment would apply value. But how to value cultural environmental services, specifically the archaeological sites? This research seeks to answer this question, as it presents the benefits of valuing these cultural services and how the immediate population to these archaeological sites can enjoy the advantages of this economic process.